Postoperative infection in penetrating versus non-penetrating glaucoma surgery. Issue 12 (5th November 2009) - Ang, Ghee Soon; Varga, Zsolt; Shaarawy, Tarek
Abstract : The aim of glaucoma surgery is to lower the intraocular pressure in order to reduce the risk of further glaucomatous progression, particularly in cases refractory to topical therapy. Although effective in reducing intraocular pressure, these procedures are not without complications, with endophthalmitis being one of the most serious. A PubMed review of the literature was performed for trabeculectomy, glaucoma drainage device procedures (Ahmed, Baerveldt and Molteno implants) and non-penetrating glaucoma surgery (deep sclerectomy and viscocanalostomy) for reports of postoperative infection, including blebitis and endophthalmitis. The literature on infections relating to non-penetrating glaucoma surgery is sparse compared with penetrating surgery, but this may be a reflection of the relatively shorter follow-up duration and comparatively smaller body of data available on non-penetrating procedures. Overall, there is not enough evidence, in terms of well-constructed randomised clinical trials with sufficiently large sample sizes and long follow-up durations, to be able to make informed comparisons of the risk of postoperative endophthalmitis and infection between the various glaucoma operations. This review article summarises the incidences of endophthalmitis from the literature and discusses the major risk factors for postoperative infection.